MUSIC THEATRE AS A PLACE OF INSIGHT. REFERENCES TO FRIEDRICH HÖLDERLIN (AND TO ARNOLD SCHÖNBERG) IN LUIGI NONO’S PROMETEO - Jörn Peter HIEKEL (Studia Universitatis Babeş-Bolyai. Musica)
Luigi Nono’s music theater work Prometeo, which is often referred to as Nono’s key work of the 1980s, dispenses with a consistently developed narrative dimension. However, it draws all the more comprehensively on the potential of several musical, literary and philosophical approaches from earlier times as well as from Nono’s own time.